Systematic regional survey and settlement patterns of the archaeological sites in the Maremani Nature Reserve, northern Limpopo Province - Antonites, Alex J. (University of Pretoria, 2022)
Dissertation (MA (Archaeology))--University of Pretoria, 2021.